2020
DOI: 10.1161/hypertensionaha.119.13368
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer-Delivered, Maternally Sequestered NF-κB (Nuclear Factor-κB) Inhibitory Peptide for Treatment of Preeclampsia

Abstract: Preeclampsia is a hypertensive disorder of pregnancy that causes significant acute and long-term risk to the mother and the baby. The multifaceted maternal syndrome is driven by overproduction of circulating anti-angiogenic factors, widespread inflammation, and endothelial dysfunction. Nuclear factor-κB (NF-κB) is a transcription factor that plays a central role in the inflammatory response. Its activity is increased in the preeclamptic placenta, and it promotes the systemic endothelial dysfunction present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
0
28
0
2
Order By: Relevance
“…Therefore, inhibition of this pathological inflammatory response with drugs with non- or low penetration into the foetal part of placenta and blood probably would reduce the risk of disturbance of beneficial NF-κB mediated processes and would ameliorate maternal symptoms. Eddy et al created an elastin-like polypeptide (ELP), associated it with NF-κB inhibitor p50i, and administered it to pregnant rats [ 78 ]. Fusion of p50i with ELP prevented its placental transfer in pregnant rats, resulting in increased deposition in the maternal kidney, liver, and placenta relative to the free peptide [ 78 ].…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inhibition of this pathological inflammatory response with drugs with non- or low penetration into the foetal part of placenta and blood probably would reduce the risk of disturbance of beneficial NF-κB mediated processes and would ameliorate maternal symptoms. Eddy et al created an elastin-like polypeptide (ELP), associated it with NF-κB inhibitor p50i, and administered it to pregnant rats [ 78 ]. Fusion of p50i with ELP prevented its placental transfer in pregnant rats, resulting in increased deposition in the maternal kidney, liver, and placenta relative to the free peptide [ 78 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Eddy et al created an elastin-like polypeptide (ELP), associated it with NF-κB inhibitor p50i, and administered it to pregnant rats [ 78 ]. Fusion of p50i with ELP prevented its placental transfer in pregnant rats, resulting in increased deposition in the maternal kidney, liver, and placenta relative to the free peptide [ 78 ]. Furthermore, in a rat model of placental ischemia, ELP-p50i partially ameliorated placental ischemia-induced hypertension and reduced placental TNF-α levels with no signs of toxicity [ 78 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…Furthermore, although we showed that the KTP-ELP construct and the fusion of KTP-ELP-VEGF target the kidney independent of the species tested [17, 18], additional studies in the swine model of RVD would be needed to characterize its biodistribution, targeting profile, and safety, as we did with ELP-VEGF [10, 11]. Still, it is important to highlight that the current study supports the plasticity of ELP technology to be fused to different therapeutic agents [10, 11, 49] as well as the possibility of applying ELP-driven strategies in other diseases [49] and in other forms of renal disease [12, 50] which offers the opportunity for more avenues of needed research towards new applications and for the progression of its potential for clinical translation.…”
Section: Limitations and Opportunitiesmentioning
confidence: 86%
“…Sham animals were incised, and vessels isolated as above, but no clips were placed. Additionally, mean arterial pressure measurements were performed on GD 19 via carotid catheter indwelling, as previously described [21] (data not shown). Animals were subsequently euthanized by isoflurane overdose, pneumothorax, and cardiac excision.…”
Section: Methodsmentioning
confidence: 99%